The value flywheel effect power the future and accelerate your organization to the modern cloud - Anderson, David; McCann, Mark; O'Reilly, Michael (IT Revolution, 2022)
Achieve rapid acceleration and transformation with the Value Flywheel Effect. Today, every business is a technology business; every leader is a technology leader. As we enter this new era, organizations must learn to harness technology to drive innovation and power change. In The Value Flywheel Effect, David Anderson, Michael O'Reilly, and Mark McCann enable leaders to create an adaptive organization built upon embracing strategic thinking, team focus, and reduced time to value to drive business results and navigate a migration to the modern cloud. Using Wardley Mapping and other sense-making approaches, The Value Flywheel Effect helps organizations anticipate market changes and user needs. As the flywheel starts to turn, each small win builds momentum. This continuous momentum builds situational awareness, breaks new boundaries, and catapults companies to sustainable, long-term success. Learn to understand and utilize the sociotechnical intersection between business, technology, and people with The Value Flywheel Effect. Give your organization the edge it needs to navigate future challenges and build maximum velocity.
Includes bibliographical references (pages 267-270) and index. - Description based on print version record
Keywords: Organizational effectiveness; Leadership; Success in business